Portfólio reflexivo: narrativas de formação inicial de professores de ciências biológicas - NEVES, Maria Aparecida (Universidade Federal do Pará, 2022)
This research was motivated by the concerns that accompany my practice, within the scope of teacher training. It aimed to understand in what terms the reflective portfolio, developed by the students, during their formative course in the Licentiate of Biological Sciences at the Federal University of Roraima, is configured as a device for the formation and constitution of teacher identity. In order to understand the meanings of what the subjects narrate, this study is based on a qualitative approach, of narrative research, together with the (auto)biographical method; understood here, not only as a knowledge or research strategy, but, rather, as a means of articulating reflection and self-knowledge associated with narrative research. With a stance of critical interpretive hermeneutics, for the analysis and treatment of biographical data, a methodology based on reflective analysis was followed, based on the paradigm of the text, proposed by Ricoeur (2002), using the hermeneutic arc. For this study, a time frame of five years was established (2014 to 2018) and the analysis corpus consisted of the portfolios provided by five graduates of the Degree in Biological Sciences at the Federal University of Roraima, whose selection took place, complying with the following inclusion/exclusion criteria: having completed the degree within the time frame and having worked or been working as a teacher for at least six months. This criterion was established due to the high number of graduates in the period. An analysis designed to define the training axes graduates as a possible training device for large companies and, for better definition, based on Josso (2004) training training, namely: Axis i; which it treats as formative experiences of/for accency; Axle ii, which deals with formative experiences for Science Teaching and; Axis iii, which deals with the experiences that form professional identity. Thus contributing, based on the epistemological theoretical assumptions embraced in this study, to the defense of the Thesis that the learner, during his formative path, in the movement of writing portfolios, manages to (re)signify his experiences, through processes of reflection on the capacity, transforming and constituting themselves in formative experiences, in this process, their professional identity trainer.